Radar principles for the non-specialist - Toomay, J. C. (John C.) 1922-; Hannen, Paul J. (Raleigh, NC SciTech Publishing, 2004)
The book is written at postgraduate level and comprises 9 chapters dealing with the following subjects: elementary electromagnetics and the radar range equation; antennas; detection and tracking; radar cross section; waveforms and signal processing; electronic countermeasures (ECM); systems applications; loose ends of radar lore; and radar potentials and limitations.
Electronic reproduction.
Keywords: Radar; Electronic books